Safety and Efficacy of the Prostar XL Vascular Closing Device for Percutaneous Closure of Large Arterial Access Sites - Christoph Thomas; Volker Steger; Stefan Heller; Martin Heuschmid; Dominik Ketelsen; Claus D. Claussen; Klaus Brechtel (Radiology Research and Practice, 2013)
Purpose. The purpose of this study is to retrospectively evaluate the efficacy and safety of the Prostar XL device for percutaneous large access site closure in an unselected patient and operator collective. Materials and Methods. All patients () who had received percutaneous vascular closing with the Prostar XL device in our institution with follow-up data of at least 6 months were retrospectively included. Primary (freedom from surgical conversion) and continued (freedom from groin surgery in further course) technical success and major (deviations from expected outcome requiring surgery) and minor (other deviations from expected outcome) complications were assessed. Success and complications rates were correlated with delivery system size (Mann-Whitney Rank Sum Tests) and operator experience (paired samples t-test). Results. Rates of primary and continued technical success as well as major and minor complications were 93.6%, 89.7%, 10.3%, and 10.3% (groin based) and 90.0%, 84.0%, 16.0%, and 16.0% (patient based), respectively. No correlation of success and complications rate was found with delivery system sizes and operator experience. Conclusions. Application of the Prostar XL device for percutaneous closure of large arterial access sites is safe with a relatively high rate of technical success and low rate of major complications. Sizes of the delivery systems and the experience of the operator did not influence the results.